Human Immunodeficiency Virus Drug Resistance (HIVDR) and Baseline Characteristics among Antiretroviral Therapy (ART) experienced Children and Adolescents under the care of Chidamoyo Christian Hospital in Hurungwe, Zimbabwe - Alfred, Makura; Kudakwashe, Mhandire; Kathrine, McCarty; Junior, Mutsvangwa; Agnes, Nhidza; Shingirai, Svinurai; David, Katzenstein; Justen, Manasa (Journal of Clinical Research In HIV AIDS And Prevention, 2023)
Introduction Human Immunodeficiency Virus (HIV) remains a persistent global public health challenge. In 2020, approximately 37.9 million individuals were living with HIV globally, including 1.7 million children <15 years old, with a global HIV prevalence of 0.8% among adults. A larger portion of people living with HIV are found in low-and middle-income countries, and Sub-Saharan Africa (SSA) is home to about 68% of people living with HIV in the world. Strikingly, with increased uptakes in PMTCT, challenges in ART programs, and high viremia among children and adolescents in SSA, the success rate of ART might be quickly compromised, with possible HIVDR emergence, particularly after years of paediatric ART exposure. Therefore, monitoring ART response in children and adolescents in terms of HIVDR patterns and other socio-economic determinants of disease progression might help achieve better treatment outcomes at individual levels. At a programmatic level, this can guide further optimization of treatment options for SSA especially Zimbabwean rural where there is paucity of information on HIVDR prevalence in children and adolescents. Methods We enrolled 89 children and adolescents experiencing virologic failure from Chidamoyo Christian Hospital in Hurungwe. We managed to amplify all the 89 using nested PCR and 32.5% (29) had resistance to at least one ART drug and analysis was done using the 29 samples. Results Among the 89 participants with virologic failure,29 were resistant to at least one of their ART drugs. 39.2% of males and 23.07% of females had HIV-1 with resistance to at least one medication. Among 29 participants with HIVDR mutations, the prevalence of at least one HIVDR mutation to protease inhibitors (PIs), Nucleotide Reverse Transcriptase Inhibitors (NRTI), and Non-Nucleotide Reverse Transcriptase Inhibitors (NNRTI) were 6.47% ,46.76% and 46.76% respectively. Of the 29 participants who had HIVDR 19 (65.5%) had resistance to a drug they were currently taking and they needed to be switched to a better effective ART regimen Conclusion Use of HIVDR testing in guiding and monitoring development of HIVDR at the start of ART or at 1st failure can be very important in treatment options and patient management.
Keywords: Human Immunodeficiency Virus; PMTCT; viremia.